Limits and Potentialities of Studying Dryland Vegetation Using the Optical Remote Sensing - Dawelbait, Mona; Morari, Francesco (Italian Journal of Agronomy, 2008)
In optical remote sensing studies, the reflectance of the vegetation canopy in arid and semiarid areas is affected by the optical properties of the vegetation elements, their arrangement in the vegetation canopy and the optical properties of the surrounding environment. The study of vegetation and surrounding environment parameters presents significant peculiarities in arid areas. Low vegetation cover leads to a small contribution of vegetation reflectance in the total pixel reflectance relative to the other materials. Most types of dry ecosystem shrubs do not differ enough from one another to allow discernment of vegetation type. Vegetation in arid and semiarid areas adapts its structure and phenology to the harsh environment, which affects the overall brightness and temporal and spatial interspecies spectral variability. Moreover, the surrounding environment in dry ecosystem influences the reflectance of the vegetation by multiple scattering and nonlinear mixing and variable spectral composition of soil surface. Many remote sensing techniques are insensitive to nonphotosynthetic vegetation, which can be a major component of total cover in dry ecosystem areas. Spectral mixture analysis (SMA) appears to be the most promising technique to obtain information on vegetation cover, soil surface type and vegetation canopy characteristics. The empirical signature libraries of the world’s dominant vegetation types could be upgraded for use with SMA.